Joint implementation for carbon–dioxide reduction in India: an analysis of auxiliary reduction in power plants. (4th August 2014) - Painuly, J.P.; Bhattacharya, K.; Parikh, J.
In view of increasing power requirements, concerns for both the local and global environment are increasing. One of the cheapest ways of reducing emissions is by efficiency improvements. India has about 120 power plants of 210 MW with auxiliary consumption ranging from 8% to 14%. Auxiliaries in a majority of the units can be upgraded to improve efficiency and reduce emissions of global as well as local pollutants. Case studies of four power plants in India have been carried out to identify possible measures to reduce auxiliary consumption. Potential carbon–dioxide emissions reductions from such modernisation of 210 MW plants are estimated to be 1.5 million tonnes per year. It is suggested that these case studies and analysis provide the basis for projects for North–South co–operation in activities implemented jointly.